Rapid Multiplex Genotyping of 20 HLA-A*02:01 Restricted Minor Histocompatibility Antigens - Romaniuk, Dmitrii S.; Postovskaya, Anna M.; Khmelevskaya, Alexandra A.; Malko, Dmitry B.; Efimov, Grigory A. (Frontiers in Immunology, 2019)
Subset of MHC-associated self-peptides presented by the recipient cells but immunologically foreign to the donor cells can induce allogeneic immune response after hematopoietic stem cell transplantation (HSCT). These immunogenic peptides originate from the genomic polymorphisms and are known as minor histocompatibility antigens (MiHA). The peptides’ disparities trigger the post-transplant immune response, which could manifest in both deleterious “graft-versus-host” disease and beneficial “graft-versus-leukemia” effect. Importantly, some MiHAs are considered as a promising target for a posttransplant T-cell immunotherapy of hematopoietic malignancies. This creates the demand for robust and fast genotyping approaches of MiHA encoding polymorphisms. Here we report a multiplex real-time PCR method for rapid genotyping of 20 polymorphisms encoding HLA*02:01 restricted MiHAs. It utilizes allele-specific primers and gene-specific hydrolysis probes and allows detection of MiHA mismatches in a donor-recipient pair without the need of electrophoresis, sequencing or other time-consuming techniques in less than one hour. The method was validated with Sanger sequencing on 5 donor-patient pairs undergoing HSCT and demonstrated good performance over a wide range of DNA concentrations. We propose our genotyping protocol as a fast and accurate method to identify mismatched MiHAs to be used both in clinical and scientific research. The information of MiHA mismatches is useful for studies of allogeneic immune response following HSCT and for target selection in a posttransplant T-cell therapy.